DIVIDEND PER SHARE, EARNINGS PER SHARE, PRICE EARNINGS RATIO, BOOK VALUE DAN FIRM SIZE TERHADAP HARGA SAHAM - DWINDA, ERIN NURUL; STELLA, STELLA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
The objective of this research to test and investigate the impact of dividend per share, earnings per share, price earnings ratio, book value and firm size on share price This research is also to compare and improve the results of prior research. Sample used in were 10 basic and chemical industry companies that passed the test of purposive sampling. Six years data have been used (2010 to 2015). Regression results show that the Price Earnings Ratio influence towards Share Price. While, Dividend per Share and Earnings per Share, Book Value and Firm Size of the companies were not influence toward Share Price.